Extrasynaptic δ‐GABAA receptors are high affinity muscimol receptors - Benkherouf AY; Taina KR; Meera P; Aalto AJ; Li XG; Soini SL; Wallner M; Uusi-Oukari M (Wiley, 2022)
Muscimol, the major psychoactive ingredient in the mushroom Amanita muscaria, has been regarded as a universal non‐selective GABA‐site agonist. Deletion of the GABAA receptor (GABAAR) δ subunit in mice (δKO) leads to a drastic reduction in high affinity muscimol binding in brain sections and loss of behavioral low dose muscimol effects. Here we use forebrain and cerebellar brain homogenates from WT and δKO mice to show that deletion of the δ subunit leads to a >50% loss of high affinity 5 nM [3H]muscimol binding sites despite the relatively low abundance of δ‐containing GABAARs (δ‐GABAAR) in the brain. By subtracting residual high affinity binding in δKO mice and measuring the slow association and dissociation rates we show that native δ‐GABAARs in WT mice exhibit high affinity [3H]muscimol binding sites (KD ~1.6 nM on α4βδ receptors in the forebrain and ~1 nM on α6βδ receptors in the cerebellum at room temperature). Co‐expression of the δ subunit with α6 and β2 or β3 in recombinant (HEK 293) expression leads to the appearance of a slowly dissociating [3H]muscimol component. In addition, we compared muscimol currents in recombinant α4β3δ and α4β3 receptors and show that δ subunit co‐expression leads to highly muscimol‐sensitive currents with an estimated EC50 of around 1‐2 nM and slow deactivation kinetics. These data indicate that δ subunit incorporation leads to a dramatic increase of GABAAR muscimol sensitivity. We conclude that biochemical and behavioral low dose muscimol selectivity for δ subunit‐containing receptors is due to low nanomolar binding affinity on δ‐GABAARs.